Design of an Optical Rotation Value Measurement Tool Using an Arduino Device: Muhammad, Beny Ragadita, and Soni Prayogi - Muhammad Muhammad; Beny Ragadita Beny Ragadita; Soni Prayogi Soni Prayogi (Jurnal Fisika dan Aplikasinya, 2023)
Malus' law asserts that the square of the cosine of the angle formed between two polarizers is directly proportional to the intensity of light after passing through them. In this study, we demonstrate this law using a straightforward configuration. Our method of measuring the polarizer's rotational angle while keeping the other polarizer stationary is innovative. It involves manually attaching a multi-turn potentiometer to one of the polarizers. The Arduino board is connected to the potentiometer and light sensor that is used to detect the intensity of transmitted light, allowing for the measurement of light intensity as a function of rotational angle. Additionally, we think that the configuration as it is now can be helpful in physics laboratory classes. It can also be demonstrated by using it during lectures